Reorganization of bird communities along a rainforest elevation gradient during a strong El Niño event in Papua New Guinea - Sam, Katerina; Jorge, Leonardo Ré; Koane, Bonny; Hazell, Richard J; Shearman, Philip L; Novotny, Vojtech (Ecology and evolution, 2024)
The El Niño 2015 event, most extreme since 1997, led to severe droughts in tropical wet Papua New Guinea (PNG), reducing May to October dry season rainfall by 75% in the lowlands and 25% in the highlands. Such droughts are likely to have significant effects on terrestrial ecosystems, but they have been poorly explored in Papua New Guinea. Here, we report changes in bird community composition prior to, during, and after the 2015 El Niño event along the elevational gradient ranging from 200 m to 2700 m a.s.l. at the Mt. Wilhelm rainforest in PNG. The abundance of birds in the lowlands dropped by 60% but increased by 40% at elevations above 1700 m during El Niño year. In the following year, the individual bird species reached mean population sizes similar to pre-El Niño years but did not fully recover. Species richness roughly followed the pattern of observed abundance and quickly and fully re-established after the event to the pre- El Niño values. Thus, at least some terrestrial birds seem to react quickly to the extreme droughts in lowlands and shift to less affected mountain habitats. We recorded upper elevational range limits to shifts by more than 500 m a.s.l. in 22 bird species (out of 237 recorded in total) during El Niño year, in contrast to their typical ranges. Our study suggests that a strong El Niño event can have strong but reversible effects on bird communities as long as they have an opportunity to move to more favorable sites through undisturbed habitats.
Keywords: feeding guilds; terrestrial birds; Mt. Wilhelm; elevational gradient; forest birds; drought; ENSO